Impact of early postoperative oral hydration in paediatric patients undergoing elective surgery after general anaesthesia. A randomised controlled trial - Mridul Dhar; Jyoti Rawat; Yashwant S Payal; Sanjay Agrawal; Ruhi Sharma; Vaishali Gupta (Indian Journal of Anaesthesia)
Background and Aims: Early feeding or oral hydration post-surgery in paediatric patients has conventionally not been encouraged, with fasting periods ranging from 3 to 6 h. The primary objective of this study was to compare the Face, Legs, Activity, Cry, Consolability (FLACC) score as a surrogate for patient satisfaction in younger children between those who received early versus delayed postoperative feeding/hydration. Secondary objectives were to compare the incidence of complications, perioperative clinical parameters and parental satisfaction. Methods: A single-blind, randomised trial was conducted in children of both genders, aged 1–5 years, undergoing elective surgery. Children were randomly allocated using sealed envelopes to receive either early hydration (EH) within 30 min of arrival to the post-anaesthesia care unit (PACU) or delayed standard hydration (SH) after 2 h. A rescue dose of fentanyl was given if the FLACC score was ≥6 at any time in PACU. The primary outcome was the FLACC score in PACU after 1 h. Statistical tests used were the unpaired t-test for normally distributed data, Mann–Whitney U test for non-normally distributed data and Fisher’s exact test for categorical variables. P < 0.05 was considered significant. Results: Out of the initially randomised 66 patients, 61 were finally analysed. Demographic and perioperative parameters were similar in both groups. FLACC score after 1 h in PACU was significantly lower in Group EH [1 (0.25–2)] than in Group SH [2 (1–3)] (P = 0.028). Parental satisfaction was higher in Group EH. There were no major complications. Conclusion: Early postoperative oral hydration is efficacious and safe compared to standard delayed feeds in children undergoing elective surgery.